Effectiveness of a Prevention Program for Gender-Based Intimate Partner Violence at a Colombian Primary School - Garzón Segura, Anni Marcela; Carcedo González, Rodrigo J. (Frontiers in Psychology, 2020)
Intimate partner violence, particularly against women, is widely studied owing to its high rates, based on transnational data. Colombia, where this form of violence is considerably common, is no exception, and such violence is occurring more and more often in increasingly younger couples (10−14 years old). Further, risk factors such as wide acceptance, the justification of intimate partner violence, extremely rigid traditional gender roles, and poor socio-emotional skills play a crucial role. In accordance with this reality, a gender-based intimate partner violence prevention program was designed, implemented, and evaluated for primary school children in Colombia based on a review of successful preventive programs and an identification of the main predictors of intimate partner violence. The program was evaluated using a quantitative study with a quasi-experimental design that included an experimental and a control group. In total, 344 participants were involved in the study: 195 boys (56.7%) and 149 girls (43.4%) from the second and third grades of a primary school (average age: 7.8 years) at a Colombian educational institution. The experimental group consisted of 200 participants and the control group of 144 participants. The program’s effectiveness was evaluated by measuring three groups of variables (gender stereotypes, the acceptance of violence, and socio-emotional skills) using reliable scales. To analyze the program’s effectiveness, mixed ANOVAs with a within-subjects factor (when the group was measured), two between-subjects factors (group and gender), and a covariate (age) were used. The results showed that the participants in the experimental group had lower scores in gender stereotypes, acceptance of peer aggression, and acceptance of physical violence against women compared to the control group. Conversely, they had higher scores in affective empathy after the intervention; both groups showed no significant differences before the intervention. This program is highly relevant because it has proven to have a positive impact on the participants and is innovative due to the lack of preventive programs that have been implemented in primary education and evaluated within the Colombian context.